Coastal erosion and sediment reworking caused by hurricane Irma – implications for storm impact on low‐lying tropical islands. Issue 4 (22nd December 2021) - Spiske, Michaela; Pilarczyk, Jessica E.; Mitchell, Stephen; Halley, Robert B.; Otai, Tiffany
Abstract: Hurricane Irma (September 2017) was one of the most devastating hurricanes in recent times. In January 2018, a post‐hurricane field survey was conducted on Anegada (British Virgin Islands) to report on the erosional and depositional evidence caused by Hurricane Irma's storm surge and waves. We document the type and extent of hurricane‐induced geomorphological changes, allowing for an improved risk assessment of hurricane‐related inundation on low‐lying islands and carbonate platforms. Anegada's north shore was most impacted by Hurricane Irma. The surge reached about 3.8 m above sea level and onshore flow depths ranged between 1.2 to 1.6 m. Storm wave action created 1 to 1.5 m high erosional scarps along the beaches, and the coastline locally retreated by 6 to 8 m. Onshore sand sheets reached up to 40 m inland, overlie a sharp erosive contact and have thicknesses of 7 to 35 cm along the north shore. In contrast, lobate overwash fans in the south are 2 to 10 cm thick and reach 10 to 30 m inland. Moreover, the hurricane reworked a pre‐existing coast‐parallel coral rubble ridge on the central north shore. The crest of the coral rubble ridge shifted up to 10 m inland due to the landward transport of cobbles and boulders (maximum size 0.5 m 3 ) that were part of the pre‐hurricane ridge. A re‐survey, 18 months after the event, assessed the degree of the natural coastal recovery. The sand along the northern shoreline of Anegada that was eroded during the hurricane and stored in the shallow water, acted as a nearshore source for beach reconstruction which set in only days after the event. Beach recovery peaked in February 2018, when beaches accreted within hours during a nor'easter‐like storm that transported large volumes of nearshore sand back onto the beach. Abstract : Storm waves and surge of Hurricane Irma (September 2017) caused both vertical and horizontal shoreline erosion, but also deposited sand sheets and washover fans onshore. A pre‐existing shore‐parallel coarse‐clast ridge was completely reworked and the ridge crest shifted several meters landward. The type and pace of coastal recovery was monitored during a re‐survey, 18 months after the hurricane.